Pneumothorax Detection System in Thoracic Radiography Images Using CNN Method - Fardana, Nouvel Izza; Isnanto, R. Rizal; Nurhayati, Oky Dwi (Universitas Negeri Semarang, 2024)
Purpose: This research aims to develop an automatic pneumothorax detection system using Convolutional Neural Networks (CNN) to classify thoracic radiography images. By leveraging CNN's effectiveness in identifying medical abnormalities, the system seeks to enhance diagnostic accuracy, reduce evaluation time, and minimize subjective interpretation errors. The output will provide a predicted label of